Applying the Social Work Health Impact Model to Child Maltreatment: Implications for Social Work Education. (3rd July 2022) - Ross, Abigail M.; Traube, Dorian; Cederbaum, Julie A.
ABSTRACT: Child abuse and neglect (CAN) is a significant and growing public health problem, yet public health approaches to eliminating CAN have not been widely embraced in the United States or in social work education. Public health approaches require a large multidisciplinary infrastructure to scale evidence-based primary prevention strategies through multiple systems. The rapid growth in the workforce projected for the next decade, combined with the increasing ubiquity of social workers across family-serving systems, position social work to be a key mechanism to implement public health approaches to CAN prevention. This article presents a rationale for expanding CAN training in social work education. We then describe the Social Work in Health Impact Model (SWHIM), an orientation to social work practice that underscores the importance of prevention and population health, and subsequently apply the SWHIM to the problem of CAN. The SWHIM suggests that social work's multilevel capacities can be enhanced, not by abandoning clinical practice but by infusing wide-lens approaches, harnessing the power of prevention, linking practice across levels, and addressing the social determinants of health. The article concludes with recommendations for U.S.-based social work education and training in CAN prevention.